Obrigado por avaliar nossos serviços: análise da qualidade do serviço de agências de receptivo por meio de comentários online - Barros, Alice Emanuele de Almeida (2023)
OBJECTIVE: This study aims to analyze how customer satisfaction of incoming travel agencies in Natal/RN is characterized, through online reviews and interviews with managers of companies in the sector. Consumer satisfaction is an essential issue for the success of organizations, especially in the current context of easy access to Information Communication Technologies and dissemination of reviews about consumer experiences. Online reviews are relevant data, which allows us to understand, through spontaneous comments, the perception of consumers about their experiences purchasing products or services. This study demonstrates the issue of consumer satisfaction in the context of incoming travel agencies, a relevant segment of tourism, specializing in receiving travelers to their destinations and offering services such as transfers, city tours, and guided tours. METHODOLOGY: This is a descriptive-exploratory research, mixed qualitative-quantitative approach, carried out through data analysis with a longitudinal time frame. The data were extracted from 843 online reviews shared by consumers of incoming travel agencies, and from interviews with the managers of 5 of 6 companies included in this search. The data were analyzed through Content Analysis and the Iramuteq Software (version 0.7 alpha 2). This study is based on Tourqual and Dailyserv models to direct the analysis of online comments, aiming to use the categories and indicators most related to the agencies’ services and the objectives proposed. RESULTS: The study shows that travelers enjoy an experience strongly linked to the categories “Human Element” (with emphasis on the performance of the Tour Guide), “Entertainment” and “Escape” proposed in the Tourqual model and to the categories “Tour guides” and “Stopover facilities”, designated in the Dailyserv model. It is inferred that consumers of incoming agencies located in Natal are satisfied with the quality of service of these companies, with actions and strategies appropriate to their clients (average rating of 4,91 and high frequency of terms referred to satisfaction in the textual corpus analyzed), the online comments are a relevant means for measuring and understanding the phenomenon studied. CONCLUSION: Through online comments, it was possible to identify indicators and categories that characterize the quality of service provided by incoming travel agencies. It is ensured that the tours, the tour guide's performance, the places visited, and the structure provided by the agencies (including vehicles and stopping places) are indicators that characterize consumer satisfaction.